СВОЙСТВА РЕЛЬЕФА: ЭКОЛОГИЧЕСКИЕ, ИНЖЕНЕРНЫЕ, ЭСТЕТИЧЕСКИЕ (ПРИГЛАШЕНИЕ К ДИСКУССИИ) - Лихачева Э.А.; Кичигин А.Н.; Палиенко В.П.; Тимофеев Д.А. (My University, 2003)
Stability and flexibility of geomorphic system form the complex of characteristics, which make possible to evaluate ecological and engineering properties of given area. Authors suggest the term "adaptation properties" of geomorphic system. The terms "engineering properties of relief", "ecological properties of relief" are posed to discussion.
Keywords: 551.4.01